Ex-vivo normothermic perfusion in renal transplantation: past, present and future. Issue 3 (June 2016) - Yong, Cissy; Hosgood, Sarah A.; Nicholson, Michael L.
Abstract : Purpose of review: Marginal donor kidneys make up a substantial proportion of transplanted kidneys. Nonetheless, they are more susceptible to injury during procurement and preservation. Normothermic perfusion is an alternative method of organ preservation that can be used to improve the quality, resuscitate, assess and potentially repair the organ. This review provides an up-to-date summary of the role of normothermic perfusion in renal transplantation and what we can expect in the future. Recent findings: Normothermic perfusion has been demonstrated to be a feasible and well tolerated method of organ preservation in a series of extended criteria donor kidneys. Furthermore, normothermic perfusion can be used as a quality assessment tool for kidneys pretransplant. In the future, normothermic perfusion could be used to manipulate the organ using gene and stem cell therapies ameliorating renal function after injury. Summary: In the last 5 years, normothermic perfusion has been translated from an experimental laboratory technique into clinical practice with promising results. Normothermic perfusion has demonstrated itself to be multifaceted in its application in renal transplantation. It may improve early graft function and can be used to assess the quality of the kidney before transplantation. The implications of these applications are crucial in maximizing the use of donor organs available in the perpetual climate of organ shortage.